Psychometric Proporties Analysis of IST (Intelligenz Structur Test) - Akmal, Nur; Widyastuti, Widyastuti; Nur, Haerani (Universitas Negeri Makassar, 2021)
This study aims to examine the characteristics of the intelligence test on the Intelligentz Structure Test (IST) version 70. The study processes were carried out to examine the psychometric characteristics of each subtest on the IST, including: item difficulty index, item discrimination index, distractor effectiveness, tool reliability measuring, and construct validity. The data sources in this study are 1112 people with undergraduate educational backgrounds from several cities in Eastern Indonesia. The results of the analysis of psychometric characteristics show that in the SE subtest there are 11 items accepted, in the WA subtest there are 13 items accepted, the AN subtest shows that 17 items are acceptable, in the GE subtest shows that all the items contained in it are still eligible to be used. In the RA subtest, 18 items are eligible to be accepted, in the ZR subtest, all items are still suitable for use, in the FA subtest, which shows 18 items are acceptable. in the WU and ME subtests, it can be seen that all items contained in them are acceptable. The reliability of the IST construct shows the omega coefficient (ÏŽ) is 0.845 and the construct validity shows that the nine subtests contained in the IST fit are based on three criteria of goodness, namely RMSEA, CFI, and TLI.